Hippo pathway-manipulating neutrophil-mimic hybrid nanoparticles for cardiac ischemic injury via modulation of local immunity and cardiac regeneration - Qiaozi Wang; Yanan Song; Jinfeng Gao; Qiyu Li; Jing Chen; Yifang Xie; Zhengmin Wang; Haipeng Tan; Hongbo Yang; Ning Zhang; Juying Qian; Zhiqing Pang; et al. (Acta Pharmaceutica Sinica B, 2023)
The promise of regeneration therapy for restoration of damaged myocardium after cardiac ischemic injury relies on targeted delivery of proliferative molecules into cardiomyocytes whose healing benefits are still limited owing to severe immune microenvironment due to local high concentration of proinflammatory cytokines. Optimal therapeutic strategies are therefore in urgent need to both modulate local immunity and deliver proliferative molecules. Here, we addressed this unmet need by developing neutrophil-mimic nanoparticles NM@miR, fabricated by coating hybrid neutrophil membranes with artificial lipids onto mesoporous silica nanoparticles (MSNs) loaded with microRNA-10b. The hybrid membrane could endow nanoparticles with strong capacity to migrate into inflammatory sites and neutralize proinflammatory cytokines and increase the delivery efficiency of microRNA-10b into adult mammalian cardiomyocytes (CMs) by fusing with cell membranes and leading to the release of MSNs-miR into cytosol. Upon NM@miR administration, this nanoparticle could home to the injured myocardium, restore the local immunity, and efficiently deliver microRNA-10b to cardiomyocytes, which could reduce the activation of Hippo-YAP pathway mediated by excessive cytokines and exert the best proliferative effect of miR-10b. This combination therapy could finally improve cardiac function and mitigate ventricular remodeling. Consequently, this work offers a combination strategy of immunity modulation and proliferative molecule delivery to boost cardiac regeneration after injury.